Pendampingan Pembelajaran Metode Yanbu’a di Pondok Pesantren Hidayatul Mustaqim Bulusari Tarokan Kediri - Ahmad i Syihab Fathon; Abd Majid Abror (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2020)
Community service is an interdisciplinary and cross-sectoral approach. For the experience of learning to conduct concrete community development activities that benefit students and the communities in which they are placed. In the field of innovation economics, the local potential to be empowered is a small business product This community assistance activity is seen as quite successful in resuscitating the community about the current environmental conditions. In mentoring also emerged good cooperation and communication between researchers and the community and the role of the community of Bulusari Tarokan Kediri Village actively in succeeding this program. And this activity can be used as a model of the implementation of religious strengthening elsewhere by adjusting the existing context.